Nut intake and 5-year changes in body weight and obesity risk in adults: results from the EPIC-PANACEA study - Freisling,H; Noh,H; Slimani,N; Chajès,V; May,AM; Peeters,PH; Weiderpass,E; Cross,AJ; Skeie,G; Jenab,M; Mancini,FR; Boutron-Ruault,M-C; et al. (European Journal of Nutrition, 2018)
PURPOSE: There is inconsistent evidence regarding the relationship between higher intake of nuts, being an energy-dense food, and weight gain. We investigated the relationship between nut intake and changes in weight over 5 years. METHODS: This study includes 373,293 men and women, 25-70 years old, recruited between 1992 and 2000 from 10 European countries in the European Prospective Investigation into Cancer and Nutrition (EPIC) study. Habitual intake of nuts including peanuts, together defined as nut intake, was estimated from country-specific validated dietary questionnaires. Body weight was measured at recruitment and self-reported 5 years later. The association between nut intake and body weight change was estimated using multilevel mixed linear regression models with center/country as random effect and nut intake and relevant confounders as fixed effects. The relative risk (RR) of becoming overweight or obese after 5 years was investigated using multivariate Poisson regressions stratified according to baseline body mass index (BMI). RESULTS: On average, study participants gained 2.1 kg (SD 5.0 kg) over 5 years. Compared to non-consumers, subjects in the highest quartile of nut intake had less weight gain over 5 years (-0.07 kg; 95% CI -0.12 to -0.02) (P trend = 0.025) and had 5% lower risk of becoming overweight (RR 0.95; 95% CI 0.92-0.98) or obese (RR 0.95; 95% CI 0.90-0.99) (both P trend <0.008). CONCLUSIONS: Higher intake of nuts is associated with reduced weight gain and a lower risk of becoming overweight or obese.